A low complexity fast converging partial update adaptive algorithm employing variable step-size for acoustic echo cancellation - Khong,AWH; Gan,W-S; Naylor,PA; Brookes,DM (2008)
Partial update adaptive algorithms have been proposed as a means of reducing complexity for adaptive filtering. The MMax tap-selection is one of the most popular tap-selection algorithms. It is well known that the performance of such partial update a.....